Evaluasi Perbandingan Pengalaman Pengguna pada Google Classroom dan LMS SMKN 3 Malang di Masa Pandemi Covid-19 menggunakan Metode Tuxel 2.0 - Elfi Atus Zahroh; Hanifah Muslimah Az-Zahra; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Due to the Covid-19 pandemic, the government recommends that students take distance learning processes. One solution to achieve learning objectives. The teacher of SMKN 3 Malang said that in the learning process two LMS were used, namely the LMS of SMKN 3 Malang and Google Classroom. However, teachers use Google Classroom more often than LMS SMKN 3 Malang because it is easier to use and looks simpler. Therefore, this study aims to determine user experience on Google Classroom, LMS SMKN 3 Malang, and compare the two LMS. As well as providing recommendations on the use of LMS SMKN 3 Malang and Google Classroom. For this reason, researchers evaluate User Experience using the Technique for User eXperience Evaluation in e-Learning (TUXEL) which consists of three aspects, namely general usability, pedagogical usability, and User Experience. The results of this study on the general usability aspect, Google Classroom found 11 problem items, compared to LMS Masterweb with 12 problem items. In the pedagogical usability aspect, 15 problem items were found in Google Classroom, while the LMS Masterweb found 18 problem items. In the User Experience aspect, Google Classroom indicates three codes consisting of: (1) support; (2) easy; (3) interesting. LMS SMKN 3 Malang also indicated four codes, namely: (1) complicated; (2) clear; (3) practical; (4) does not meet expectations